2019
DOI: 10.1111/febs.14840
|View full text |Cite
|
Sign up to set email alerts
|

Rev1 plays central roles in mammalian DNA‐damage tolerance in response to UV irradiation

Abstract: Rev1, a Y‐family DNA polymerase, is involved in the tolerance of DNA damage by translesion DNA synthesis (TLS). Previous studies have shown that the C‐terminal domain (CTD) and ubiquitin (Ub)‐binding (UBM) domains of Rev1 play important roles in UV‐damage tolerance, but how these domains contribute to the process remains unclear. In this study, we created Ub mutations in a proliferating cell nuclear antigen (PCNA)‐Ub fusion that differentially affect its interaction with Rev1 and Polη and found that UV‐damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
(98 reference statements)
1
12
0
Order By: Relevance
“…In mammalian cells, deletion of REV1 leads to exacerbation of oxidative stress, cell senescence, and apoptosis (41). Furthermore, elevated expression of Rev1 confers enhanced UV damage tolerance (42). In our study, the deletion of REV1 caused a severe growth defect, whereas overexpression of REV1 enhanced cell growth compared to that of the wild-type strain under oxidative stress; this could be due to the mutagenic nature of Rev1.…”
Section: Discussionmentioning
confidence: 47%
“…In mammalian cells, deletion of REV1 leads to exacerbation of oxidative stress, cell senescence, and apoptosis (41). Furthermore, elevated expression of Rev1 confers enhanced UV damage tolerance (42). In our study, the deletion of REV1 caused a severe growth defect, whereas overexpression of REV1 enhanced cell growth compared to that of the wild-type strain under oxidative stress; this could be due to the mutagenic nature of Rev1.…”
Section: Discussionmentioning
confidence: 47%
“…Since Rev1 interacts with Polη and Rev7 through its Rev1-CTD that can be further divided into two subdomains 34 , 35 , we screened a large number of reported point mutations in this region 34 , 35 , 38 , 39 and identified four mutations either specifically affecting Polη but not Rev7 binding (L1170A and V1188A), or disrupting Rev7 but not Polη binding (Y1242A and L1246A). By using an RPA nuclear focus formation assay as an indication of TLS activity after UV irradiation 37 , 40 , it was found that Rev1-L1170A and Rev1-V1188A protected cells to a level comparable to that of Rev1, while CTD-Y1242A and CTD-L1246A lost Rev1 functions 36 (Supplementary Fig. S1 ), which indicates that DDT provided by Rev1 does not require its physical interaction with Polη.…”
Section: Resultsmentioning
confidence: 99%
“…The Rev1-CTD contains two separate domains to interact with Y-family polymerases including Polη, Polι and Polκ, and the Rev7 subunit of Polζ 32 35 . We recently attempted to address detailed scaffold roles of Rev1 in response to UV-induced DNA damage and surprisingly found that UV damage tolerance conferred by ectopic expression of Rev1 is dependent on its interaction with Rev7 but independent of Polη interaction 36 . The current study further addressed genetic and physical interactions between Rev1 and Polη, which allowed us to conclude that the Rev1 polymerase can play a backup role in the absence of Polη and that Polη requires its RIR motifs to protect cells from UV-induced DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the cell cycle regulation of Rev1 (Waters and Walker 2006 ) and Pol eta (Plachta et al 2015 ) levels under stress-free conditions has indicated similarities in the cell cycle regulation patterns of these two polymerases. However, a common regulatory strategy has seemed less obvious in cells treated with DNA-damaging agents, since Pol eta and Rev1 can play distinct roles in TLS and other processes linked to the maintenance of DNA stability (Prakash et al 2005 ; Hirano and Sugimoto 2006 ; Acharya et al 2019 ; Niu et al 2019 ). Accordingly, in the promoter of the RAD30 gene, which encodes Pol eta, two DNA damage responsive elements ( DREs ) have been recognized (McDonald et al 1997 ), and increases in RAD30 mRNA levels in response to UV radiation have been reported by several laboratories (McDonald et al 1997 ; Pabla et al 2008 ; Wiltrout and Walker 2011a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this unique enzymatic activity, Rev1 plays a more general function in TLS as a scaffold protein for other TLS polymerases. In both yeast and mammalian cells, Rev1 functionally and physically interacts with B-family TLS polymerase zeta (Pol zeta) (Acharya et al 2006 ), which is important for the majority of Pol zeta-mediated spontaneous and DNA damage-induced mutagenesis in dividing (Prakash et al 2005 ; Haracska et al 2001a , b ; Niu et al 2019 ; Szwajczak et al 2018 ) as well as stationary yeast cells (Halas et al 2009 ). Additionally, Rev1 interacts with other Y-family polymerase members in both yeast (Acharya et al 2007 ) and higher eukaryotes (Guo et al 2003 ; Ohashi et al 2004 ; Kosarek et al 2008 ), and these interactions facilitate the recruitment of these polymerases to the DNA replication machinery and stimulate TLS mechanisms engaging more than one polymerase.…”
Section: Introductionmentioning
confidence: 99%